How is information in working memory selected and prioritised for action? - Printzlau, FAB (2021)
Flexible cognition necessary for everyday behaviour depends on working memory (WM)–the ability to keep information in mind for a later use. Not all items in WM are represented equally. Attention can be allocated to select and prioritise task-relevant content for a forthcoming action.